A geo‐spatial approach to assess Trees outside Forest (ToF) in Haryana State, India. (20th April 2021) - Kumar, Mothi; Kumar, Ritesh; Bishnoi, Promila; Sihag, Vikas; Bishnoi, Ravikant; Rani, Seema; Sindhu, Partibha; Budhwar, Sarika; Kumar, Parmod; Sharma, Shashikant; Sharma, Poonam; Sharma, Ritu; et al.
Abstract: Mapping and monitoring the Trees outside Forest (ToF) is gaining significance in the scientific community as they provide critical ecosystem services such as protecting soil and water resources, wildlife habitat, and aesthetics including food, fuel, and fibre. Quantifying ToF can also provide useful information for emission estimation relating to the agriculture, forests, and other land use (AFOLU) category of the Intergovernmental Panel for Climate Change (IPCC). Despite the importance of quantifying ToF, very few studies have attempted to quantify them in India's natural resource inventory programs. In this study, we focused on Haryana State, India, to inventory ToF using very high‐resolution (VHR) Indian Remote Sensing (IRS) satellite data. Haryana's landscape is interspersed with croplands and ToF, thus providing a challenging environment to test VHR satellite data's ability to quantify the diversified landscape structure. We specifically used CARTOSAT‐1 panchromatic (2.5 m) and multispectral LISS‐IV (5.8 m) datasets to quantify the vegetation and build a much‐needed database for ToF. We used a novel classification scheme based on the geometry, that is, point, line, or polygon formations, to quantify ToF at a scale of 1:10, 000. The obtained results suggest ToF with linear and block formations extended to 128.83 and 20.51  km 2, respectively, accounting for ~3.38% of the Total Georgraphical Area of Haryana State while point formations established 2, 774, 531 in numbers. This study highlights the usefulness of VHR satellite data and fused imagery to quantify ToF in highly diverse landscape of Haryana. The results will help address vital ecosystem services from ToF, including greenhouse gas emissions quantification from the Agriculture, Forests and Other LandUse (AFOLU) category.